2019
DOI: 10.3390/ma12111753
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Scale Surface Patterning of Titanium Dental Implants by Anodization in the Presence of Modifying Salts

Abstract: The bone-implant interface influences peri-implant bone healing and osseointegration. Among various nano-engineering techniques used for titanium surface modification, anodization is a simple, high-throughput and low-cost process, resulting in a nanoporous oxide coating which can promote osseointegration and impart antimicrobial and immunomodulatory properties. We anodized rounded tip dental implants of commercial grade titanium in aqueous phosphoric acid modified with calcium and potassium acetate, and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Without pretreatment, anodization will only produce microporous on the Ti surface, which is formed from immersion with NaOH at high temperatures for a long time [10,[18][19][20]. Several studies have shown that anodization can produce a nano-surface [21,22]. Our previous study [10] also demonstrated that the Ti subjected to the HF pretreatment with different current densities showed the formation of a hierarchical porous (micro and nano-porous) surface.…”
Section: Discussionmentioning
confidence: 95%
“…Without pretreatment, anodization will only produce microporous on the Ti surface, which is formed from immersion with NaOH at high temperatures for a long time [10,[18][19][20]. Several studies have shown that anodization can produce a nano-surface [21,22]. Our previous study [10] also demonstrated that the Ti subjected to the HF pretreatment with different current densities showed the formation of a hierarchical porous (micro and nano-porous) surface.…”
Section: Discussionmentioning
confidence: 95%
“…TiO 2 nanotubes may undergo specific changes by changing the anodizing process conditions, such as pH, temperature, applied potential, current density, anodizing time, acid concentration, and different morphological parameters (height, surface, and diameter) [33]. Usually, the anodizing of titanium is done by introducing it in an aqueous or organic electrolytic medium (in the component of which fluorine ions are found), applying a constant voltage [34]. Therefore, due to the incorporation of fluoride into the anodizing electrolyte, the increased surface roughness and the ability to stimulate mechanically, NTT cells are compatible with bone cell function, even in the absence of drugs [35].…”
Section: Electrochemical Anodizingmentioning
confidence: 99%
“…In particular, smoking is also considered among the main risk factors for the onset of periodontitis [ 21 , 22 ]. Similarly, peri-implantitis, which is a microbially initiated destructive inflammation of the tissues surrounding dental implants which eventually determines bone loss until implant loss [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], shares common etiopathogenic pathways with periodontitis [ 30 ] and is also negatively affected by habitual smoking [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%